Incidence of the soil mechanization over the physical properties and the vegetative growth of papaya (Carica papaya L.) - Mendez V., Diego Fernando; Becerra O., Luís Carlos; Hernández N., Héctor Eduardo; Díaz I., Anthony José; Muñoz M., Alfonso Julián (Revista de Ciencias Agrícolas, 2016)
In order to determine the incidence of the soil mechanization over its physical properties and the vegetative growth of papaya in Florencia (Caquetá), it was used a randomized block design with three treatments: mechanized soil with motor-hoe, hoe and no mechanized – control with four repetitions each. The resistance to the penetration, and vegetative growth indexes were measured in the field while the total porosity and apparent density were calculated in the lab. In the first month (M1) the resistance to the penetration showed significant difference (p<0,05) to 0-10 cm depth. The apparent density presented significant difference (p<0,05) to 0-10 and 10-20 cm depth between SMMTA related to SMAS and no mechanized, which did not exhibit significant differences at any depth. The apparent density and the resistance to the penetration increased with the time. The greatest values of production assimilates and light energy absorption performance represented in the net assimilation rate, were observed in the witness 180-days after planting, when it reached 10,04 gm-2day-1. The duration of the leaf area and growth rate of the crop were the variable more sensitive to changes of the porosity and resistance to the penetration of the soil. The witness treatment reached the highest levels of net assimilation rate, probably due to the homogeneity of the assimilated gains through the photosynthetic time evaluated.